Effect of Feed Supplement with Different Dosage on the Growth and Survival of Siamese Catfish Seedling - Meriyanti Muharam; Juliana Juliana; Mulis Mulis (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2019)
This study aims to determine the effect of addition of VITERNA Plus with different doses in feed on growth and survival seed Siamese catfish (Pangasius hypophthalmus). This research using the experimental method, with a completely randomized design (CRD) and 4 treatment 3 replicates. Results show that the highest growth in length and weight indicated in treatment D of 1.86 cm and 0.72 grams, C 1, 65 cm and 0.62 grams, and 1.23 cm and 0.42 grams and the lowest growth, namely in treatment A 0.67 cm and 0.25 gram. Survival of Siamese catfish seed during treatment A showed 66.67 %, amounting to 76.19% of treatment B, treatment C amounting to 80.95% and amounted to 88.10% in treatment D. Results of analysis of variance in length and weight of the seed of Siamese catfish show that different doses VITERNA Plus have very real effect with the value of F Calculation of the length and weight are 65.57 and 105.46, while the value of F table (0.01) is 7.59. Keywords: feed; supplement; Siam Catfish; Pangasius hypophthalmus; seed; survival; dosage, growth